Measurement of dijet azimuthal decorrelations at central rapidities in pp̄ collisions at s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, D. L.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahmed, S. N.; Ahn, S. H.; Alexeev, G. D.; et al. (American Physical Society (APS), 2005)
Correlations in the azimuthal angle between the two largest transverse momentum jets have been measured using the D0 detector in pp̄ collisions at a center-of-mass energy s=1.96TeV. The analysis is based on an inclusive dijet event sample in the central rapidity region corresponding to an integrated luminosity of 150pb-1. Azimuthal correlations are stronger at larger transverse momenta. These are well described in perturbative QCD at next-to-leading order in the strong coupling constant, except at large azimuthal differences where contributions with low transverse momentum are significant. © 2005 The American Physical Society.